JFB – Trends in Food Bioactives - Fereidoon Shahidi; Adriano Costa de Camargo (Journal of Food Bioactives, 2019)
Food bioactives are important components found in (functional) foods and are responsible for (perceived) health benefits to human health, either as such or their metabolites.  The Journal of Food Bioactives had its second year successfully reporting on different aspects of functional food ingredients in 4 volumes and as such captured the attention of those in the field. This report provides a cursory account of selected examples to illustrate this fact.